(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The rapid evolution of transportation, energy, and aerospace technologies continues to increase the demand for aluminum alloys with superior combinations of strength, ductility, and thermal stability. Meeting these requirements relies on a deep understanding of the microstructural mechanisms governing deformation and strengthening. Over the last decade, substantial advancements have been achieved in the development of multiscale strengthening strategies, where atomic-level solute interactions, nanoscale precipitates, and submicron grain structures are engineered synergistically to optimize mechanical performance. This review consolidates recent experimental and theoretical progress in precipitation engineering, solute–dislocation interactions, and grain refinement through SPD. A comparative assessment of strengthening efficiency, stability under service temperatures, and applicability to industrial-scale processing is provided. The article also outlines remaining challenges and identifies promising routes toward designing next-generation aluminum alloys optimized for lightweight, high-performance structural applications.